A probabilistic identification of the buckling resistance of imperfect cylindrical shells in axial compression - Sadovský, Z.; Kriváček, J.; Sokol, M. (Engineering structures, 2024)
The buckling resistance of imperfect circular cylindrical shells of elastic and isotropic material subject to axial compression is studied focusing on initial geometric imperfections. Considering the imperfections as a random field, the suggested probabilistic representation of the buckling resistance parallels the deterministic dependence of buckling loads on the size and shape of imperfections. It derives from the probability density function of an imperfection size measure and the conditional probability density functions of the resistance confined to the realizations of imperfections given their size levels. The separated representation of the buckling resistance allows: (1) supplementary checking the accuracy of the random field representation, (2) classifying measured and simulated imperfections by their size and shape effects on buckling loads, (3) prospective delimiting the range of working imperfections for fabrication tolerance classes, and (4) defining the characteristic imperfection for the semi-probabilistic design. Introductory calculations illustrate the dependence of the normalized buckling loads of a shell on the shape and size of imperfections. •Shells in axial compression considering geometric imperfections as a random field.•A probabilistic representation of the buckling resistance of the imperfect shells.•Separating the size and shape effects of imperfections on the buckling resistance.•Supplementary checking the accuracy of a random field representation.•Defining the characteristic imperfection for the semi-probabilistic design.